CODE SWITCHING DAN CODE MIXING PADA NOVEL CRYING WINTER KARYA MELL SHALIHA - Susylowati, Eka (University of Brawijaya, 2023)
ABTRACTThe purpose of this study describes the types of code switching and code mixing in Mell Shaliha Crying Winter novel and the factors that cause code switching and code mixing. The method used in this research is qualitative method. This study uses a qualitative method. Data collection is done by observation and note-taking. The results of this study explain that code switching and code mixing events in the novel Crying Winter are found, namely internal and external code switching in the form of English into Indonesian and vice versa, Korean into Indonesian and the phenomenon of code mixing in the form of words, phrases, baster and clauses. The factors that influence the existence of code switching and code mixing are the participants, the situation, and the influence of the previous speech, and the aims of the conversation.Keywords: code switching, code mixing, Crying Winter novel